A Tutorial On Mean-Field-Type Games and Risk-Aware Controllers. (2020) - Barreiro-Gomez, Julian; Tembine, Hamidou
Abstract: This paper presents a tutorial of the role that mean-field-type games play in the design of risk-aware controllers. The tutorial is presented in an easy-to-follow manner for beginners, engineers and early career scientists. It starts by introducing a basic stochastic mean-field-free control design problem and progressively adds more complexity to the problem setup navigating through the risk-aware control design, stochastic differential games, mean-field games, and concluding with mean-field-type games. All the problems are solved in a semi-explicit way by means of the direct method and some engineering applications, such as water distribution system and consensus under uncertainties, illustrate the performance of the presented risk-awareness framework.